Benefits of forests in Cameroon: global structure, issues involving access and decision-making hiccoughs - Oyono, P.R.; Kouna, C.; Mala, W.A. (2005)
Among many other stakes, the economic stake derived from the exploitation of tropical forest resources is a burning issue. This is evidenced by insecurity in intergenerational access to forest resources and financial benefits relating to the latter, on the one hand, and by a deep iniquity at the intra-generational level, on the other hand. The following paper highlights, as a moral, social and policy dilemma, how stakeholders and generations, ‘self-interested’, mark out access to forest resources and to financial benefits relating to the latter. Through intensive participatory research, quantitative data collection, participant observation, future scenarios and some International Forestry Research's social science methods and interactive games (SSM & IG) based on the evaluation of the sustainability of forest management systems, field research conducted in the forest zone of Cameroon on access to forest resources has generated two central results. Firstly, future generations will be confronted—in a dramatic way—to quantitative and qualitative scarcity of forest resources, following their over exploitation by present generations. Secondly, as concerns the intra-generational access benefits generated by commercial exploitation of forests and the assessment of the circulation of forestry fees, there is much inequity, in as much as those benefits are more profitable to a ‘forestry elite’—‘a self-interested block’—than to local communities, who strongly claim to have historical rights over these forests. As a contribution of social science to public knowledge and to policy development, this article is nourishing ‘rational choice’ and ‘rational egoism’ theory and is targeting decision-making processes in the ever first attempt of forest management decentralization and ‘legal’ benefits sharing in Central Africa (the second largest forest of the World). The article recommends the shortening of the distance between decision-making and beneficiaries, downwardly accountability, ‘bottom-up’ mechanisms of public dialogue in forest management and a collaborative infrastructure in the circulation and the distribution of forest benefits.